2016
DOI: 10.21037/jss.2016.09.07
|View full text |Cite
|
Sign up to set email alerts
|

Surfer’s myelopathy: a rare presentation in a non-surfing setting and review of the literature

Abstract: Background: Surfers myelopathy can be a rapidly devastating disease and little is known surrounding the pathophysiology of the condition. Although the classical pattern of illness has been well reported, it has never been observed in a non-surfing setting.Methods: A 51-year-old demolition worker presented with acute non-traumatic myelopathy. Clinical examination revealed sensory loss to the level of L2. T2-MRI and MRI-DWI revealed a hyperintense signal suggestive of an ischaemic event. A diagnosis of surfer's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…As a result of her imaging findings and history, she was diagnosed with SM. Maharaj et al 5 reported a 51-year-old with the same clinical and MRI findings but without a history of spinal hyperextension.…”
Section: Discussionmentioning
confidence: 96%
“…As a result of her imaging findings and history, she was diagnosed with SM. Maharaj et al 5 reported a 51-year-old with the same clinical and MRI findings but without a history of spinal hyperextension.…”
Section: Discussionmentioning
confidence: 96%
“…Previous case reports and series have reported age-ranges for affected individuals between 7 [6] and 51 [5]. Our patient is therefore the oldest reported case of SM, and the only reported with pre-existing vertebral pathology.…”
Section: Discussionmentioning
confidence: 52%
“…Cases of non-traumatic spinal cord ischaemia have been described in surgical patients with an intra-operative hyperlordotic posture [4], demolition workers [5], cheerleaders [6], acute spinal hyperextension [7], and clearly (usually novice) surfers [1,8], but never before in swimmers.…”
Section: Discussionmentioning
confidence: 99%
“…Among case reports of surfer's myelopathy without surfing, we found three reports of four cases, by searching PubMed with the key words “surfer's myelopathy” and “without surfing.” In addition, Segami et al . reported cases that resemble surfer's myelopathy .…”
Section: Discussionmentioning
confidence: 99%